2020
DOI: 10.3390/jcm9092824
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on the Severity of Clinicopathologic Parameters in Patients with IgA Nephropathy

Abstract: Several studies reported the effect of obesity on the progression of IgA nephropathy (IgAN). However, the impact of obesity on the clinicopathologic presentation of IgAN remains uncertain. This is a retrospective cross-sectional study from eight university hospitals in South Korea. Patients were categorized into three groups using the Asia-Pacific obesity classification based on body mass index (BMI). Clinical and histopathologic data at the time of renal biopsy were analyzed. Among 537 patients with IgAN, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Additionally, Wu et al showed that high BMI was associated with a higher risk of interstitial fibrosis [ 28 ]. In our eight-center affiliation study, obesity was an independent risk factor for mesangial expansion [ 29 ]. In our study, clinical variables including BMI and HTG independently increased the risk of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Wu et al showed that high BMI was associated with a higher risk of interstitial fibrosis [ 28 ]. In our eight-center affiliation study, obesity was an independent risk factor for mesangial expansion [ 29 ]. In our study, clinical variables including BMI and HTG independently increased the risk of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MEST-C scoring system roughly reflects the extent of tissue damage in a way that scores with 0 and 1 (M, E, S) or 0, 1, and 2 (T) for each item. For this reason, we analyze key histological damage mentioned above with a more specialized hospital consensus scoring system [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent epidemiologic studies noted that high BMI was a risk factor for chronic comorbidities, including hypertension, type 2 diabetes mellitus, dyslipidemia, cardiovascular disease, chronic kidney disease (CKD), and cancer. 2,4 CKD was shown to be the second common cause of obesity-related mortality only next to cardiovascular disease. Obesity has drawn more attention as a prognostic factor for CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental researches have also demonstrated obesity-related glomerulopathy, which is characterized by glomerulomegaly, thickening of glomerular basement membrane (GBM), mesangial matrix expansion, and focal segmental glomerulosclerosis. 4,6 CKD is defined as the structural or functional alterations of the kidney that persists for three or more months. Immunoglobulin A nephropathy (IgAN) is the most common primary glomerular disease worldwide, which results in CKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation